ORCHID PESTS AND THEIR PESTS METHODS OF FIGHTING - Khurramova Munira Ahmad kizi, (International Journal of Innovations in Engineering Research and Technology, 2023)
In this article, aphids causing damage in intensive orchards, absorbent such as shackles, spiders, shields, shackles, against sucking pests by studying pest bioecology information about the fight is provided.